ANALISA KEPATUHAN WAJIB PPH PASAL 21 DALAM RANGKA PENINGKATAN PENERIMAAN NEGARA PADA KANTOR PELAYANAN PAJAK PRATAMA PALEMBANG ILIR TIMUR - . Asmuni (Fakultas Ekonomi Universitas Tridinanti Palembang, 2019)
ABSTRACT This study aims to determine the level of compliance of Article 21 Income Tax Payers at Palembang Ilir Timur Tax Office. The data used is secondary data. Data collection techniques using literature and documentation.Data analysis is done quantitatively by using data tabulation. Qualitatively, namely explaining the results of quantitative analysis and the results of evaluation of the socialization of the new tax law that has been carried out by Palembang Ilir Timur KPP Pratama.The results of the study concluded that: 1) Compliance with taxpayers, Palembang Ilir Timur Pratama KPP in making PPh 21 payments in a timely manner for 2013-2014 can be categorized as non-compliant taxpayers and taxpayer compliance in the delivery and completeness of 21-year PPh SPT 2013-2014 can be categorized as a compliant taxpayer. 2) Dissemination The new tax law by Palembang Ilir Timur KPP Pratama has been quite good but has not been routinely carried out due to the size, costs needed for the socialization activities. Keywords: Mandatory Compliance and Dissemination of Taxation Law